MANAJEMEN LABORATORIUM KOMPUTER DALAM PENINGKATAN PRESTASI PESERTA DIDIK BIDANG AKADEMIK DI MTs SALAFIYAH SYAFI’IYAH TEBUIRENG JOMBANG - NABILA HIMMATUL ‘ULYA; ASEP KURNIAWAN (Kampus Akademik Publiser, 2024)
Laboratory management has various meanings according to the background of the definition. However, it can be understood that laboratory management is the process of good management of the place where computer practicum activities take place as an approach to learning information and communication technology. The laboratory is an academic equipment besides books and other media. The focus of this research is 1. How is the management of the computer laboratory at MTs Salafiyah Syafi’iyah Tebuireng Jombang 2. How is academic achievement increased at MTs Salafiyah Syafi’iyah Tebuireng Jombang 3. How is the management of the computer laboratory in increasing student achievement in academic fields in MTs Salafiyah Syafi’iyah Tebuireng Jombang.This research uses a descriptive qualitative research approach with a case study type of research. Data collection techniques are observation, interviews and documentation. Then the data obtained was analyzed using data reduction, data presentation, drawing conclusions and verification.The results of this research show that 1) computer laboratory management at MTs Salafiyah Syafi’iyah Tebuireng Jombang includes several activities, namely planning, equipment arrangement, administration, maintenance and supervision. 2) increasing student learning achievement at MTs Salafiyah Syafi’iyah Tebuireng Jombang really accommodates students needs according to their talents and interests. 3) computer laboratory management in increasing student achievement at MTs Salafiyah Syafi’iyah Tebuireng Jombang is going very well due to the huge influence of technology, especially computers, in the process of increasing student achievement.